2009
DOI: 10.1080/15389580903191617
|View full text |Cite
|
Sign up to set email alerts
|

Toward a More Parsimonious Approach to Drug Recognition Expert Evaluations

Abstract: The findings from this study will facilitate the process of identifying the correct category of drug ingested by focusing on critical signs and symptoms of drug influence. This work will have direct and immediate relevance to the training of drug recognition experts (DREs) by providing the foundation for an innovative, statistically based approach to drug classification decisions by DREs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…These findings appear in line with previous studies that have reported a relation between impairment on the SFST and presence of THC in blood. A study that assessed which signs of the Drug Evaluation and Classification evaluations predicted various drug categories (including cannabis) at best showed that OLS contributed significantly to the prediction, but HGN and WAT did not (Porath-Waller et al 2009). Papafotiou et al (2005a) assessed SFST performance in 40 healthy participants who received low and high doses of THC in a placebo-controlled study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings appear in line with previous studies that have reported a relation between impairment on the SFST and presence of THC in blood. A study that assessed which signs of the Drug Evaluation and Classification evaluations predicted various drug categories (including cannabis) at best showed that OLS contributed significantly to the prediction, but HGN and WAT did not (Porath-Waller et al 2009). Papafotiou et al (2005a) assessed SFST performance in 40 healthy participants who received low and high doses of THC in a placebo-controlled study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on scientific and medical knowledge about the known signs and symptoms associated with various drugs, the DEC program is a systematic and standardized 12-step procedure used by trained law enforcement officers, known as drug recognition experts (DREs), to recognize and evaluate behaviors and physiological indicators associated with 7 different drug categories: Central nervous system (CNS) depressants, inhalants, dissociative anesthetics, cannabis, CNS stimulants, hallucinogens, and narcotic analgesics. The results of the 12-step protocol, when corroborated by toxicological evidence of drug use, provide sufficient evidence to proceed with drug-impaired driving charges (Beirness and Porath 2017;Porath-Waller et al 2009).…”
Section: Introductionmentioning
confidence: 87%
“…The officer then assesses these data to determine whether the subject is impaired and which drug category or categories are most likely responsible for the impairment. The amount of information is extensive and some have questioned whether the number of pieces of information collected is too large to reasonably consider in rendering an opinion about the class of drug involved (Schechtman and Shinar and Schechtman 2005) and that it may be possible to initially focus on a core set of measures from the evaluation without significantly compromising accuracy (Porath-Waller and Beirness 2010;Porath-Waller et al 2009). Because the DEC evaluation provides evidence of impairment and drug influence, it is important that the opinion of the evaluating officer in terms of drug category is accurate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Recent data suggest that approximately 5% of Canadian drivers/adults report driving after cannabis use in the past year. 39 Large-scale epidemiological studies using different methodologies (e.g., retrospective epidemiological and case control studies) have found that cannabis use acutely increases the risk of motor vehicle accident (MVA) involvement and fatal crashes among drivers. 40,41 Recent reviews have found the increase in risk to be approximately 1.5-3.0, an increase which is substantially lower, however, than that in alcoholimpaired drivers.…”
Section: Cannabis Use and Drivingmentioning
confidence: 99%